MAPKs activation in head and neck squamous cell carcinomas - Daniele Maggioni; Renato Gaini; Gabriella Nicolini; Giovanni Tredici; Werner Garavello (Frontiers Media S.A., 2011)
Cancer of head and neck (HN) represents a diffused group of neoplasia; despite advances in clinical treatment its mortality rate has remained high, mainly because it is frequently diagnosed only at an advanced stage. Molecular markers allowing the diagnosis at an early stage would be useful. Mitogen-activated protein kinases (MAPK) are a family of protein kinases, which transduces extracellular stimuli into intracellular responses, controlling proliferation, differentiation and apoptosis. Given their key role in the regulation of cell survival and proliferation, MAPKs have been deeply studied in cancer. Furthermore, they are of particular interest in HN cancer progression, since they are downstream of one of the most frequently found alterations in this cancer: the over-expression of the epidermal growth factor receptor. Although a deregulation of MAPK expression and activation has been reported in several type of cancers, data regarding their role in HN cancer progression are contrasting, thus the aim of this short review is to summarize the data from literature regarding MAPKs activation in this type of cancer.